Conflict resolution in the workplace : a study of culture and gender in an international company - Moiseeva, Anastasiia; Martínez Pantoja, Yadira Ixchel; Kloudová Jiřičková, Václava; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
Organizational life will inevitably involve conflict, which can negatively affect workers’ satisfaction, mental state, and overall performance. Specifically concentrating on the impact of culture and gender inside an international company, the goal of this thesis is to investigate conflict resolution trends in the workplace. This study aims to increase knowledge about how culture and gender variables affect conflict resolution processes. The research methodology employed in this thesis is qualitative, focusing solely on interviews with employees. This qualitative approach focuses on employee perspectives on conflict, cultural norms, and gender-related events. Through these interviews, the study explores employees' opinions, conflict-resolution strategies, and personal experiences. This study intends to investigate whether and how values, norms, and communication styles affect conflict resolution strategies through the analysis of the data gathered. The research will explain how culture, gender, and conflict resolution are related, giving knowledge to firms willing to implement more effective conflict management. The findings of the study will enhance the knowledge that already exists on conflict resolution. The purpose of this study is to offer companies useful suggestions for enriching their cultural and gender sensitivity and conflict resolution tactics. The results of this study will help create a workplace that is more productive and peaceful.
Vedoucí práce: Yadira Ixchel Martínez Pantoja
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses